2011
DOI: 10.1177/1559827610387236
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influences on Physical Activity Behavior in Children and Adolescents: A Brief Review

Abstract: Given the widespread problem of physical inactivity and the continued growth in the prevalence of childhood and adolescent obesity, promotion of regular physical activity among youth has become a public health priority. Abstract: Understanding the social and environmental factors that influence physical activity is important in the development of effective interventions to increase physical activity behavior in children and adolescents.One factor that has received considerable research attention is the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
175
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(207 citation statements)
references
References 114 publications
18
175
1
13
Order By: Relevance
“…According to reviews, previous studies have shown contradictory results in terms of the associations between parental influence and children's PA: parental support in the form of encouragement and involvement is constantly reported as being in association with children's PA whereas the possible association between the children's and parents' PA has been inconsistent [20,21]. The results of this study are partly similar as in other studies using the YPAP model as a theoretical background.…”
Section: Discussionsupporting
confidence: 90%
“…According to reviews, previous studies have shown contradictory results in terms of the associations between parental influence and children's PA: parental support in the form of encouragement and involvement is constantly reported as being in association with children's PA whereas the possible association between the children's and parents' PA has been inconsistent [20,21]. The results of this study are partly similar as in other studies using the YPAP model as a theoretical background.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, 12 review papers have examined the association between child's PA and parent's PA (for review see (Yao and Rhodes, 2015)). Three of 12 studies do not support the link between child's PA and parent's PA (Trost and Loprinzi, 2011;Bauman, et al, 2012;Sterdt, et al, 2013) while eight of them found the relationship inconclusive (Sallis, et al, 2000;Biddle, et al, 2005;Gustafson and Rhodes, 2006;Van Der Horst, et al, 2007;Edwardson and Gorely, 2010;Craggs, et al, 2011;Biddle, et al, 2011;Webber and Loescher, 2013). Due to different findings, more research on this topic is needed.…”
Section: Introductionmentioning
confidence: 96%
“…rétroaction positive) et la disponibilité des aliments à la maison [30]. Une revue systématique de Trost et Loprinzi (2011) aborde dans le sens du rôle déterminant de la famille, alors qu'on a révélé que les parents jouaient un rôle déterminant sur la pratique d'activités physiques des adolescents [31]. Cependant, il y a peu de données québécoises quant aux influences spéci-fiques de ces trois environnements (école, pairs, famille) sur les comportements des jeunes « sportifs », ainsi qu'aux différences particulières desdits environnements sur les adolescents engagés dans une pratique sportive.…”
Section: Introductionunclassified